SHARKS AND RAYS IN INDONESIA - Fahmi, - (Research Center for Oceanography - Indonesian Institute of Sciences (LIPI), 2010)
Indonesia is considered to have a high diversity of sharks and rays due in part to its position in the equatorial line, between two continents and two oceans. According to recent studies and various publications, the number of chondrichthyan species known to date is 207 species of 44 families, comprised of 109 species of sharks, 96 species of batoids, and two species of ghost sharks (chimaera). The Dasyatidae (stingrays) is the most speciose family of chondrichthyans occurring in Indonesia, followed by the Carcharhinidae (whaler sharks). Most species of elasmobranchs commonly occur on the continental or insular shelves and rays are more commonly found than sharks. This type of habitat can be found mostly in the western part of Indonesia (the Java Sea, Karimata Strait, South China Sea, Malacca Strait, and Macassar Strait). Due to the separation by the Wallace Line, there are some differences in species diversity between western and eastern region. The shark and ray fauna of the eastern region is more similar to the Australian fauna, while the fauna in the western region is more similar to the Asian fauna. There are also some endemic species known to occur in Indonesian waters. The endemicity of some species can be restricted in a certain area or in a regional area such as the Indo-West Pacific.